Potret lesbian butch dalam novel detik terakhir karya alberthiene endah: kajian sosiologi sastra - Ega Setia Nanda; Yenni Hayati (Universitas Ahmad Dahlan, 2020)
This study aims to describe the portrait of butch lesbians in the novel Detik Terakhir by Alberthiene Endah. This type of research used in research is qualitative research with descriptive methods. The data in this study are in the form of words, phrases, clauses, and sentences that describe lesbians in the form of narrator narratives, and figures analyzed from characterizations and plot. Data collection techniques are: reading and understanding the novel Detik Terakhir by Alberthiene Endah, identifying, and data inventory. The data validation technique used in the study is the triangulation technique. Data analysis techniques used in this study are: classifying relevant data, interpreting data, providing a critical view of the results of the analysis, and making conclusions from the data that has been obtained and writing the results of the analysis. The results in this study describe a lesbian butch who is affected by parents who are not harmonious, traumatized in childhood, and the environment. In this research, a person who is butch can not only be seen from the way he is dressed, looks by cutting his hair like a man, and has the nature of wanting to protect and be compassionate for the woman he loves.